Teknologi Pengeditan Gen pada Anemia Sel Sabit (Sickle Cell Disease) : CRISPR-Cas9, Base Editing, dan Prime Editing - Fadhilah, Nurul; Hartati, Hartati (Biocaster : Jurnal Kajian Biologi, 2026)
Sickle Cell Disease (SCD) is a monogenic disease due to a point mutation in the HBB gene that causes chronic hemolytic anemia and vaso-occlusive crisis, while conventional therapy is generally palliative. In the past decade, CRISPR-based gene editing has developed rapidly and given birth to three main platforms, namely CRISPR-Cas9, base editing, and prime editing which opens up opportunities for more curative therapies through fetal hemoglobin (HbF) reactivation or correction of genetic targets. This literature review aims to compare working principles, cutting-edge achievements, advantages, and limitations, as well as the ethical implications and potential integration of biology learning from the three technologies. The method used is a descriptive-comparative literature review of 2015-2025 publications from reputable databases (PubMed, Scopus, ScienceDirect, SpringerLink, and Nature Portfolio) which is selected based on relevance and quality. The results of the synthesis showed that CRISPR-Cas9 has reached the clinical stage through HbF-enhanced autotemcel (exa-cel/Casgevy) exagamglogen therapy and is reported to suppress vasoocclusive crises in most patients. Base editing offers base change without Double-Strand Break (DSB) and shows promising preclinical results, including HbS conversion strategies into antisickling variants (e.g. HbG-Makassar) as well as modulation of HbF regulators. Prime editing provides the ability to "rewrite" sequences without DSBs or separate DNA donors and shows preclinical evidence in hematopoietic stem cells and animal models, but efficiency, complexity of delivery, and long-term safety data remain challenges. This study emphasizes that strengthening ethical governance (safety, informed consent, and access fairness) needs to go hand in hand with innovation. In addition to biomedical relevance, the topic of SCD-gene editing has the potential to be an authentic context for developing students' genomic literacy, ethical reasoning, and critical thinking through the PjBL and SSI approaches.